WOUND HEALING ACTIVITY OF LEMON PEPPER ESSENTIAL OIL IN BURN WOUND OF WISTAR RAT - PURNAMA, DEWI; GINTING, CHRISMIS NOVALINDA; CHIUMAN, LINDA; KHU, ADRIAN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The purpose of the study was to investigate the acceleration of the wound healing properties from lemon pepper’s essential oil as the lemon pepper’s ointment. Methods: There were 20 Wistar rats as an animal trial divided into four sample groups, including control (ointment base), standard (Nebacetin®), 5% lemon pepper, and 10% lemon pepper ointment, and all groups were injured by electric soldier for 10 s. The wound contraction and epithelialization period were the parameters of wound healing activity. Result: Wound contraction as the parameter of wound healing showed significant difference between the standard and lemon pepper ointment (p<0.05). The lemon pepper ointment groups showed no significant wound contraction difference in each lemon pepper ointment concentration at the initial time of observation, however, it become more obvious at last period of observation. Furthermore, the epithelialization period did not showed any significant differences between standard, 5% or 10% lemon pepper ointment against the control group (p>0.05). Conclusion: It can be concluded that the lemon pepper ointment had the potential to accelerate wound healing activity.